Pharmacognostical standardization of leaves of Cupressus macrocarpa Hartweg. ex Gordon - Sudhir K. Thukral, Sumitra Singh, Surendra Kr. Sharma (Journal of Applied Pharmaceutical Science, 2014)
Cupressus macrocarpa Hartweg. ex Gordon belongs to family Cupressaceae. It is commonly known as Monterey Cypress. Traditionally the decoction of leaves is used in rheumatism. The species of genus Cupressus are used to improve bladder tone and coadjuvant in therapy of urinary incontinence and enuresis. The present study was carried out to establish the pharmacognostical study along with preliminary phytochemical screening of petroleum ether, chloroform, ethanol and aqueous extracts of Cupressus macrocarpa. The macroscopical and microscopical characters of leaves were studied. The transverse section of leaves indicated the arrangement of various cells in epidermis, sunken stomata, hypodermis, spongy parenchyma and vascular bundles. The physico-chemical parameters such as total ash, acid insoluble ash, water soluble ash and sulphated ash value, loss on drying, extractive values, fluorescence analysis of extracts and powder treated with different chemical reagents were studied under ordinary light, short and long UV light. The foaming and swelling index of leaves were also studied. Preliminary phytochemical screening of various extracts revealed the presence of glycosides, flavonoids, sterols, phenolic compounds, carbohydrates and amino acids. These studies will be helpful in developing standards for quality, purity and sample identification of this plant.
Keywords: Cupressus macrocarpa, Cupressaceae, pharmacognostical, physico-chemical parameters.